Genomic and clinical characterization of pulmonary‐only metastatic prostate cancer: A unique molecular subtype. Issue 13 (7th August 2019) - Shenderov, Eugene; Isaacsson Velho, Pedro; Awan, Anas H.; Wang, Hao; Mirkheshti, Nooshin; Lotan, Tamara L.; Carducci, Michael A.; Pardoll, Drew M.; Eisenberger, Mario A.; Antonarakis, Emmanuel S.
Abstract: Background: Isolated pulmonary involvement is uncommon in metastatic hormone‐sensitive prostate cancer (mHSPC). To characterize outcomes and molecular alterations of this unique patient subset, we conducted a retrospective review of patients with hormone‐naïve prostate cancer presenting with lung‐only metastases. Methods: This was a retrospective single‐institution study. Medical records of 25 patients presenting with pulmonary‐only metastases before receiving androgen deprivation therapy (ADT) were analyzed. Germline and/or somatic genomic results, where available (n = 16), were documented. Tumor tissue was analyzed using clinical‐grade next‐generation DNA sequencing assays. Clinical endpoints included complete prostate‐specific antigen (PSA) response to ADT (<0.1 ng/mL), median overall survival (OS) from time of ADT initiation, median PSA progression‐free survival (PSA‐PFS), and failure‐free survival (FFS) at 4 years. Results: Baseline characteristics were notable for 48% of men (12 of 25) having first or second‐degree relatives with prostate cancer, compared with 20% expected. Complete PSA responses to ADT were noted in 52% of men, with a median PSA‐PFS of 66 months, a 4‐year FFS rate of 72%, and a median OS that was not reached after 190 months. In evaluable patients, molecular drivers were enriched for mismatch repair mutations (4 of 16, 25%) and homologous‐recombination deficiency mutations (4 of 16, 25%). These results are limited by the small sample size and retrospective nature of this analysis. Conclusions: This exploratory study represents one of the largest cohorts of lung‐only mHSPC patients to‐date. The prevalence of actionable DNA‐repair gene alterations was higher than anticipated (any DNA‐repair mutation: 8 of 16, 50%). Compared to historical data, these patients appear to have exceptional and durable responses to first‐line ADT. This study suggests that pulmonary‐tropic mHSPC biology may be fundamentally different from nonpulmonary mHSPC.